The Influence of Financial Literacy and Social Media Exposure on Skincare Product Expenditure Patterns among University Students - Hade Chandra Batu Bara; Baihaqi Ammy; Ade Gunawan (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
University students increasingly allocate funds to skincare products, reflecting the influence of both financial literacy and social media exposure on their spending behavior. This study aims to analyze the individual and combined effects of these factors on skincare product expenditure patterns among students at the University of Muhammadiyah North Sumatra (UMSU). A quantitative associative design was employed, with data collected from 101 purposively sampled UMSU students who actively use social media and purchase skincare products. Multiple linear regression, t-tests, F-tests, and determination coefficients (R²) were applied to examine relationships. Results show that financial literacy significantly influences expenditure patterns (t = 10.296; p 0.001; b = 0.621), and social media exposure also has a significant positive effect (t = 2.914; p = 0.004; b = 0.170). Simultaneously, both factors significantly predict expenditure behavior (F = 200.217; p 0.001), explaining 80.4% of the variance (R² = 0.804). The findings highlight the importance of strengthening financial literacy while fostering critical awareness of social media influences to promote responsible consumption behavior among university students. Universities are encouraged to integrate financial literacy programs into student development initiatives to promote rational and responsible consumption in the digital era.